Phenotyping congenital anomalies in administrative hospital records. Issue 1 (20th January 2020) - Zylbersztejn, Ania; Verfürden, Maximiliane; Hardelid, Pia; Gilbert, Ruth; Wijlaars, Linda
Abstract: Background: Congenital anomalies are a major cause of co‐morbidity in children. Diagnostic code lists are increasingly used to identify congenital anomalies in administrative health records. Evidence is lacking on comparability of these code lists. Objectives: To compare prevalence of congenital anomalies and prognostic outcomes for children with congenital anomalies identified in administrative health records using three different code lists. Methods: We developed national cohorts of singleton livebirths in England (n = 7 354 363, 2003‐2014) and Scotland (n = 493 556, 2003‐2011). Children with congenital anomalies were identified if congenital anomaly diagnosis was recorded at birth, during subsequent hospital admission or as cause of death before 2 years old. We used three code lists: the EUROCAT list for congenital anomaly surveillance in Europe; the Hardelid list developed to identify children with chronic conditions (including congenital anomalies) admitted to hospital in England; and the Feudtner list developed to indicate children with complex chronic conditions (including congenital anomalies) admitted to hospitals in the United States. We compared prevalence, and risks of postnatal hospital readmission and death according to each code list in England and Scotland. Results: Prevalence of congenital anomalies was highest using the EUROCAT list (4.1% of livebirths in England, 3.7% in Scotland), followed by Hardelid (3.1% and 3.0% of livebirths, respectively) and Feudtner (1.8% and 1.5% of livebirths, respectively). 67.2%‐73.3% of children with congenital anomalies in England and 65.2%‐77.0% in Scotland had at least one postnatal hospital admission across the three code lists; mortality ranged between 42.6‐75.4 and 41.5‐88.7 deaths per 1000 births in England Scotland, respectively. The risk of these adverse outcomes was highest using Feudtner and lowest using EUROCAT code lists. Conclusions: The prevalence of congenital anomalies varied by congenital anomaly code list, over time and between countries, reflecting in part differences in hospital coding practices and admission thresholds. As a minimum, researchers using administrative health data to study congenital anomalies should report sensitivity analyses using different code lists.